STUDI KELAYAKAN PUSAT KULINER TERAPUNG TANJUNG MERPATI DI KABUPATEN BURU SELATAN, PROVINSI MALUKU - Laitupa, Jamilang; Mulyandari, Hestin (Universitas Aisyiyah Yogyakarta, 2019)
South Buru Regency, as a part of the Maluku Islands Province. This natural tourist attraction has the potential to be developed into a tourist destination so as to increase tourist visits and the contribution of the tourism sector in South Buru Regency. Needing for the feasibility study of the Tanjung Merpati Floating Culinary Center Design in South Buru Regency, Maluku which supported with Neo Vernacular Architecture method. It is to improve the economy of the local community and provide recreation for tourists such as fishing and other tourism. It is different from other culinary in South Buru Regency, because of Neo Vernacular analysis so that it gets a response to the design.